Pain as an alarm signal in cervical carotid dissection: report of a case with catastrophic evolution - Valença, Marcelo Moraes; Valença, Martina Falcão; Valença, Marcelo Andrade; Leitão, Laécio Batista; Valença, Luciana Patrízia Alves de Andrade; Silva-Néto, Raimundo Pereira (Headache Medicine, 2023)
Background Cervical carotid dissection is a commonly reported arteriopathy and is associated with stroke in young, healthy patients. Case report The authors present a case of a woman with pain of recent onset secondary to a dissection of the cervical segment of the carotid artery on the same side and that evolved with stroke. Conclusion The diagnosis of arterial dissection is based on clinical suspicion and angiographic images of the encephalic vessels.